End-of-Life Care Related Distress in the PICU and NICU: A Cross-Sectional Survey in a German Tertiary Center - Garten, Lars; Danke, Andrea; Reindl, Tobias; Prass, Anja; Bührer, Christoph (Frontiers in Pediatrics, 2021)
Objective: To investigate and compare nurses’ perceived care-related distress and experiences in end-of-life situations in neonatal and pediatric intensive care units. Study design: Single-center, cross-sectional survey. Administration of an anonymous self-report questionnaire survey to nurses of two tertiary neonatal intensive care units (NICUs), and two tertiary pediatric intensive care units (PICUs) in Berlin, Germany. Results: Seventy-three (73/227, response rate 32.2%) nurses completed surveys. Both, NICU (32/49; 65.3%) and PICU (24/24; 100.0%) nurses, reported “staffing shortages” to be the most frequent source of distress in end-of-life situations. However, when asked for the most distressing factor, the most common response by NICU nurses (17/49) was “lack of clearly defined and agreed upon therapeutic goals”, while for PICU nurses (12/24) it was “insufficient time and staffing”. No significant differences were found in reported distress-related symptoms in NICU and PICU nurses. The interventions rated by NICU nurses as most helpful for coping were: “discussion time before the patient’s death” (89.6%), “team support” (87.5%), and “discussion time after the patient’s death” (87.5%). PICU nurses identified „compassion“ (98.8%), “team support”, “personal / private life (family, friends, hobbies)” and “discussion time after the patient’s death” (all 87.5%) as most helpful. Conclusions: Distress-related symptoms as a result of end-of-life care were commonly reported by NICU and PICU nurses. The most frequent and distressing factors in end-of-life situations might be reduced by improving institutional/organizational factors. Addressing the consequences of redirection of care, however, seems to be a more relevant issue for the relief of distress associated with end-of-life situations in NICU, as compared to PICU nurses.